Pemberdayaan Pemuda dalam Pengelolaan Limbah Kayu Bernilai Ekonomis di Desa Kemantren Kecamatan Jabung - Febi Dwi Widayanti; Indria Kristiawan (Sasambo: Jurnal Abdimas (Journal of Community Service), 2020)
Utilization of wood waste has many benefits with cheap raw materials, easy to obtain and if used as a unique product it will have a selling value and is very beneficial for the community because it has a variety of different types of products and functions. One source of waste that can be utilized is waste produced from cutting logs taken in the middle. Utilization of wood waste into works of art that will be able to increase youth income and reduce wood waste produced. Artworks made from wood waste in the form of decorative lamps, key chains, wall hangings, photo frames, stationery places. Utilization of wood waste can increase the income of young people who work as temporary laborers and be able to open their own jobs by turning wood waste into works of art that have economic value.